Strategies and Challenges In Teaching Vowel Digraphs For EFL Learners: A Systematic Literature Review - Rizky Anugrah Putra; Moh. Fahruddin Aziz; Herlandri Eka Jaya Putri (Applied Linguistics: Innovative Approaches and Emerging Trends, 2026)
English vowel digraphs pose significant challenges for English as a Foreign Language learners due to deep orthographic irregularities and native language interference. This systematic literature review investigates teachers' challenges and material preparation strategies for mitigating these linguistic barriers. Following PRISMA guidelines, 74 articles across major databases were rigorously screened, yielding 8 highly relevant peer-reviewed studies for thematic synthesis. The analysis reveals a critical phonetic gap; notably, studies show that most of EFL students lack adequate grapheme-phoneme knowledge for digraph decoding. To mitigate this, educators are abandoning native-centric textbooks in favor of targeted pedagogical strategies. Integrating technology-enhanced language learning tools and explicit phonics instruction significantly improves decoding accuracy. Furthermore, bespoke phonics-based pronunciation innovations demonstrated high efficacy, has significant instructional efficiency scores in targeted classrooms. Ultimately, overcoming orthographic barriers requires explicit phonetic instruction and the localized development of bespoke, technology-enhanced teaching materials to master irregular spelling patterns.